Generation Alpha - Merensiana Hale (EDULEAD: Journal of Christian Education and Leadership, 2022)
Generation Alpha is a new generation that is present in the midst of society and the church has unique characteristics. By having broad insight into the Alpha generation, child servants, teachers and parents are greatly assisted in educating and nurturing the Alpha generation. This book provides a number of insights about the Alpha generation from describing their characteristics and needs, to how to nurture and educate them, even to predicting their future so that it can be anticipated early on. AbstrakGenerasi Alpha adalah generasi baru yang hadir di tengah- tengah masyarakat dan gereja memiliki karakteristik yang unik. Dengan memiliki wawasan yang luas mengenai generasi Alpha para pelayan anak, guru dan orang tua sangat dibantu dalam mendidik dan mengasuh generasi Alpha. Buku ini menyajikan sejumlah wawasan mengenai generasi Alpha mulai dari gambaran karakteristik dan kebutuhan mereka, sampai pada cara mengasuh dan mendidik mereka, bahkan sampai pada memprediksi masa depan mereka sehingga dapat diantisipasi sejak dini.